Pembaruan Hukum Perdata sebagai Upaya Meningkatkan Keadilan Gender - Roem, Anwar M.; Payzon Aituru, Yulianus; Zirhani Rumalean, Zonita; Muslim, Muslim (UNES Law Review, 2024)
The reform of civil law plays a crucial role in guiding society towards better gender justice. This article investigates the impact of civil law reform on women's empowerment and the enhancement of gender equality across various aspects of life. The primary focus involves analyzing legal changes aimed at addressing gender disparities in civil rights, property ownership, and family responsibilities. The discussion includes evaluating the impact of civil law reform on traditional structures that may limit women's roles. Additionally, this article highlights concrete steps taken to provide stronger legal protection for women, encouraging active participation in social and economic life. Through an interdisciplinary approach, the article also reviews the psychological and social impacts of civil law reform on societal perceptions of gender roles. Thus, the author argues that civil law reform is not only about legal reform but also a critical step towards a more just and equal society. In conclusion, civil law reform is not merely a legal necessity but also a catalyst for profound social change. This article hopes to stimulate further discussion on how legal efforts can continue to promote gender equality within a broader legal framework.